The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/1462-2920.14354
|View full text |Cite
|
Sign up to set email alerts
|

Resistant ammonia‐oxidizing archaea endure, but adapting ammonia‐oxidizing bacteria thrive in boreal lake sediments receiving nutrient‐rich effluents

Abstract: SummaryClimate change along with anthropogenic activities changes biogeochemical conditions in lake ecosystems, modifying the sediment microbial communities. Wastewater effluents introduce nutrients and organic material but also novel microbes to lake ecosystems, simulating forthcoming increases in catchment loadings. In this work, we first used 16s rRNA gene sequencing to study how the overall sediment microbial community responds to wastewater in six boreal lakes. To examine forthcoming changes in the lake b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
3
11
0
Order By: Relevance
“…These results agree with those from a previous study in the Gulf of Mexico (Newell et al, 2014), where benthic AOA communities were less diverse following Hurricanes Ike and Gustav, suggesting a weak resistance to disturbance. Increased AOB abundance in our study also supports disturbance studies in boreal lake sediments (Aalto et al, 2018) and estuaries (Happel et al, 2018), where AOB diversity and/or abundance increased at affected sites, suggesting that AOB are more adaptable to disruptive events (Aalto et al, 2018).…”
Section: Ammonia-oxidizer Community Structure and Abundancesupporting
confidence: 86%
See 2 more Smart Citations
“…These results agree with those from a previous study in the Gulf of Mexico (Newell et al, 2014), where benthic AOA communities were less diverse following Hurricanes Ike and Gustav, suggesting a weak resistance to disturbance. Increased AOB abundance in our study also supports disturbance studies in boreal lake sediments (Aalto et al, 2018) and estuaries (Happel et al, 2018), where AOB diversity and/or abundance increased at affected sites, suggesting that AOB are more adaptable to disruptive events (Aalto et al, 2018).…”
Section: Ammonia-oxidizer Community Structure and Abundancesupporting
confidence: 86%
“…Sequences longer than 555 bp for AOA, and 475 bp for AOB, and low-quality sequences with more than one mismatch in barcode/primer sequences, were removed in Mothur. Frameshift errors in unique archaeal and bacterial reads were corrected using the FunGene FrameBot tool (Wang et al, 2013), and sequence alignment was conducted using aligned archaeal or bacterial amoA sequences retrieved from the FunGene database (Aalto et al, 2018). Chimeric sequences were removed using Uchime in Mothur (Edgar et al, 2011), and sequences were clustered into OTUs at 95% sequence identity.…”
Section: Amoa Amplicon Sequencing and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These authors found that ammonia oxidation rates were completely different when AOA activities were dominant over AOB. Aalto et al () also showed that nitrification would be promoted by increasing AOB communities with increases in nutrient loadings in lake ecosystems. Therefore, microbial composition and their abundances were very important to their functional resistance and resilience, and their changes would alter the ecosystem function by changing the process rates.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies reported that microbial composition was not connected with the prediction of microbial functions so that the composition cannot estimate the microbial resistance and resilience to ecosystem disturbance related to the ecosystem function and service aspects (Nannipieri et al, ; Sjöstedt, Langenheder, Kritzberg, Karlsson, & Lindström, ). However, some researchers have found that microbial composition was very important to the ecosystem processes, especially for the process rates (Aalto, Saarenheimo, Mikkonen, Rissanen, & Tiirola, ; Allison & Martiny, ; Baho, Peter, & Tranvik, ; Galand et al, ). Interestingly, de Vries et al () demonstrated that the bacterial community was not associated with ecosystem respiration under drought conditions, but was directly associated with ecosystem respiration after 1 week of rewetting.…”
Section: Discussionmentioning
confidence: 99%